2004
DOI: 10.1007/s00066-004-1337-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dose-Volume Histograms after Prostate Seed Implantation

Abstract: A learning curve characterized by an increase in the D90post can be observed and results in a stable technique after 18 patients. An important factor influencing the learning curve in addition to the precision of seed positioning is organ volume definition on postimplant imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Using TPSI, besides the experience of the implanting team an optimal treatment technique in TPSI is essential [13]. Grimm et al [10] implanted 125 patients between 1988 and 1990 and reported a follow-up of 10 years (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Using TPSI, besides the experience of the implanting team an optimal treatment technique in TPSI is essential [13]. Grimm et al [10] implanted 125 patients between 1988 and 1990 and reported a follow-up of 10 years (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Permanent interstitial brachytherapy with 125 I or 103 Pd seed implants is a common treatment for early-stage prostate cancer [7,10,11,16]. Computed tomography-(CT-)based dosimetry is currently recommended as the standard for postimplant dosimetry [1,8,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Current options for the treatment of organ-confined prostate cancer include radical surgery, photon-based external-beam therapy, brachytherapy or special treatment options such as proton radiotherapy [2,8,12,15,18,20,21,28,30,38].…”
Section: Introductionmentioning
confidence: 99%